2004
DOI: 10.1096/fj.03-1088fje
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol induces proliferation of keratinocytes via receptor‐ mediated mechanisms

Abstract: In this study, we investigated the effects of estradiol on the proliferation of neonatal keratinocytes, the expression of estrogen receptor isoforms, and the signaling mechanisms by which estradiol mediates cell growth. We demonstrate that estradiol binds neonatal keratinocytes with high affinity (Kd=5.2nM) and limited capacity (Bmax of 14.2fmol/mg of protein), confirming the presence of estrogen binding sites. Using specific antibodies, we demonstrate that keratinocytes express both estrogen receptor (ER)-alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 75 publications
2
81
0
3
Order By: Relevance
“…This is further supported by another group who demonstrated that incubation of cultured human epidermal keratinocytes with estradiol increased phosphorylation levels of ERK1 and ERK2 kinases within 15 minutes (Verdier-Sevrain et al 2004).…”
Section: The Epidermissupporting
confidence: 62%
See 2 more Smart Citations
“…This is further supported by another group who demonstrated that incubation of cultured human epidermal keratinocytes with estradiol increased phosphorylation levels of ERK1 and ERK2 kinases within 15 minutes (Verdier-Sevrain et al 2004).…”
Section: The Epidermissupporting
confidence: 62%
“…Another study has demonstrated mRNA and protein for ERβ and not ERα is expressed in cultured human epidermal keratinocytes Watanabe 2003a, 2003b), while a different group have shown that both ERα and ERβ are expressed in cultured human neonatal foreskin keratinocytes (Verdier-Sevrain et al 2004). These differences may be due to differences in anatomical site, since the number of estrogen receptors has been shown to differ with anatomical site, with face skin homogenates having a greater number of receptors than breast or thigh skin (Hasselquist et al 1980).…”
Section: The Epidermismentioning
confidence: 98%
See 1 more Smart Citation
“…Estrogen receptor β (ERβ) is strongly expressed in the human stratum basal and spinosum of the scalp epithelium (29) and the increase in ERα expression is induced by estrogen in keratinocytes (30). SLPI regulates the proliferation of human endometrial epithelial cells and is expressed strongly to promote the proliferation of carcinoma cells (16,17,31).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, decreased estrogen levels associated with menopause correlate with epidermal thinning, and estrogen containing skin creams have been shown to increase epidermal thickness (Fuchs et al 2003, Hall & Phillips 2005. The E2 induces proliferation of neonatal keratinocytes in vitro, which express both ERa and ERb (Verdier-Sevrain et al 2004). ERb was expressed by many cell types in skin from the human scalp, while ERa was localized to the dermal papilla and sebocytes (Thornton et al 2003).…”
Section: Discussionmentioning
confidence: 99%